1975
DOI: 10.1042/bj1500329
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of rat liver tyrosine aminotransferase by tetracycline

Abstract: Rat liver tyrosine aminotransferase was purified 200-fold and an antiserum raised against it in rabbits. 2. Hepatic tyrosine aminotransferase activity was increased fourfold by tyrosine, twofold by tetracycline, 2.5-fold by cortisone 21-acetate and ninefold by a combination of tyrosine and cortisol administered intraperitoneally to rats. 3. Radioimmunoassay with 14C-labelled tyrosine aminotransferase, in conjunction with rabbit antiserum against the enzyme, revealed that cortisol stimulates the synthesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Reynolds & Thompson (1974) obtained similar results, but observed that enzyme inactivation was preceded by a lag period of about 1 h during which the enzyme activity was stable. Seubert & Hamm (1975) have reported that ATP inhibits the rapid inactivation of tyrosine aminotransferase in the presence of 5mM-cysteine and Hannah & Sahib (1975) observed rapid inactivation of purified tyrosine aminotransferase in the presence of a crude lysosome fraction and l0mM-cysteine. The purpose of the present study was to investigate further the role of cysteine in the inactivation of tyrosine aminotransferase in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds & Thompson (1974) obtained similar results, but observed that enzyme inactivation was preceded by a lag period of about 1 h during which the enzyme activity was stable. Seubert & Hamm (1975) have reported that ATP inhibits the rapid inactivation of tyrosine aminotransferase in the presence of 5mM-cysteine and Hannah & Sahib (1975) observed rapid inactivation of purified tyrosine aminotransferase in the presence of a crude lysosome fraction and l0mM-cysteine. The purpose of the present study was to investigate further the role of cysteine in the inactivation of tyrosine aminotransferase in vitro.…”
mentioning
confidence: 99%
“…The inactivation of tyrosine aminotransferase (L-tyrosine-2-oxoglutarate aminotransferase, EC 2.6.1.5) in cell-free systems at neutral pH has been investigated in several laboratories (Auricchio et al, 1972;Reynolds & Thompson, 1974;Hannah & Sahib, 1975;Seubert & Hamm, 1975), and may reflect reactions in the intracellular turnover of this enzyme. A common factor in these systems in vitro has been the addition of cysteine.…”
mentioning
confidence: 99%